1994
DOI: 10.1109/49.298058
|View full text |Cite
|
Sign up to set email alerts
|

Multicarrier orthogonal CDMA signals for quasi-synchronous communication systems

Abstract: Abstracf-We propose a multicarrier orthogonal CDMA signaling scheme for a multiple-access communication system, such as the reverse channel of a cellular network, as an alternative to the multi-user interference cancellation approach. The average variance of cross-correlations between sequences is used as a measure for sequence design. We search for sets of sequences that minimize the probability of symbol detection error, given that there is imperfect synchronization among the signals, that is, the signals ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
92
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(92 citation statements)
references
References 13 publications
0
92
0
Order By: Relevance
“…An alternative, and yet computationally efficient, form can be expressed in the frequency domain by using the inverse Fourier representation of signals and their HSR as SNR (25) where the effect of PN spreading sequences are averaged out. Similarly, the SNR expression for the SL receiver is SNR (26) where the SL receiver is evaluated by setting in .…”
Section: Signal-to-noise Ratiomentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative, and yet computationally efficient, form can be expressed in the frequency domain by using the inverse Fourier representation of signals and their HSR as SNR (25) where the effect of PN spreading sequences are averaged out. Similarly, the SNR expression for the SL receiver is SNR (26) where the SL receiver is evaluated by setting in .…”
Section: Signal-to-noise Ratiomentioning
confidence: 99%
“…In the reverse link, however, only quasi-synchronism can be achieved with the aid of a timing reference. Quasi-synchronous CDMA signals can be modeled with chip delays chosen from a probability distribution function , which is nonzero in for [25]. For instance, in wideband CDMA (WCDMA) systems, all users are synchronized within in the reverse link to reduce intracell interference [26].…”
Section: Cmentioning
confidence: 99%
“…In these MC-CDMA schemes, the transmitter of both multitone based direct-sequence CDMA [3] (multitone DS-CDMA) and that of orthogonal multicarrier DS-CDMA (MC DS-CDMA) [2], [5] spreads the serial-to-parallel converted data streams using a given spreading code in the time domain. In a multitone DS-CDMA system the subcarrier frequencies are chosen to be orthogonal harmonics of each other with minimum frequency separation among them before DS spreading [3], which is expressed as for (1) where represents the symbol duration of the multitone DS-CDMA signal, while and are the subcarrier frequencies and initial phases, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The subcarrier frequencies hence take the form of for , where is the number of subcarriers and is the fundamental frequency. By contrast, in an orthogonal MC DS-CDMA system, the subcarrier frequencies are chosen to satisfy the orthogonality condition with the minimum possible frequency separation after DS spreading [1], [2], [5], which can be expressed as for (2) which implies that the spacing between two adjacent subcarrier frequencies is , where is the chip duration of the DS spreading codes and the subcarrier frequencies take the form of for . Let be the spreading gain of the DS-spread subcarrier signals.…”
Section: Introductionmentioning
confidence: 99%
“…Frequency diversity in MC-CDMA systems is usually achieved by repeating the transmitted signal in the frequency (F)-domain with the aid of several subcarriers [4], [5], [7]. Classic studies of MC-CDMA have shown that the various MC-CDMA schemes proposed in the literature [2]- [7] are capable of supporting multiple users communicating over frequency-selective fading channels.…”
Section: Introductionmentioning
confidence: 99%